Trichoderma sp . Cultivation Training as a Natural Fungicide at the Green Lawu Forest Farmer Group in Berjo Village, Karanganyar - Jaya, Christian Arief; Bahri, Saepul; Aprilliano, Daniel Briliana; Trianto, Irvan; Siswijonarko, Mohamad Imam Dimas (Universitas Negeri Semarang, 2025)
Use substance chemistry in a way continously can cause accumulation residue in the soil , which is potential cause effect harm for environment . Therefore that , training intended For improve skills in groups farmer Green Lawu forest in Berjo Village , Karanganyar , in cultivation mold Trichoderma sp. as fungicide natural . Training done through method counseling that includes making starter media using Potato Dextrose Agar (PDA), and multiplication become product powder Ready use with flour media rice and bran . Training results show improvement understanding participant to benefit Trichoderma sp. , good as controller organism the bully plants (OPT) and as booster growth plants . In addition , training This succeed reduce dependence farmers on materials chemistry agriculture that is not friendly environmental and expensive. It is hoped that this program can push adoption Trichoderma sp. in a way sustainable For support system agriculture friendly environment in Berjo Village .